Relationship between DNA damage and sperm head birefringence - Petersen, C. G. [UNESP]; Vagnini, L. D.; Mauri, A. L.; Massaro, F. C.; Cavagna, M.; Baruffi, R. L. R.; Oliveira, J. B. A. [UNESP]; Franco, J. G. [UNESP] (Elsevier B.V., 2011)
Birefringence or double refraction is the decomposition of a ray of light into two rays when it passes through an anisotropic material such as quartz. Sperm cells have been demonstrated to be optically anisotropic. The objective of this study was to evaluate the relationship between the pattern of human sperm head birefringence (SHBF) and DNA damage. A total of 26 patients with normal semen were included. DNA damage (fragmentation and denaturation) was evaluated in the sperm head in the context of birefringence, both total (SHBF-T) and partial (SHBF-P), by terminal deoxyribonucleotidyl transferase (TdT)-mediated dUDP nick-end labelling assay and acridine orange fluorescence, respectively. Positive DNA fragmentation in spermatozoa with SHBF-T (205/1053; 19.5%) was significantly higher (P < 0.0001) than in spermatozoa that presented SHBF-P (60/820; 7.3%). However, the percentage of denatured DNA in spermatozoa with SHBF-T (824/1256; 65.6%) was not significantly different from the ones with SHBF-P (666/1009; 66.0%). In conclusion, the data support a positive relationship between spermatozoa with total SHBF in their head and increased DNA fragmentation. (C) 2011, Reproductive Healthcare Ltd. Published by Elsevier Ltd. All rights reserved.
Keywords: DNA denaturation; DNA fragmentation; MSOME; sperm birefringence; sperm DNA damage; sperm selection